In Vitro and In Vivo Characterization of Selected Fluorine-18 Labeled Radioligands for PET Imaging of the Dopamine D3 Receptor - Nebel, Natascha; Maschauer, Simone; Kuwert, Torsten; Hocke, Carsten; Prante, Olaf (Molecules, 2016)
Cerebral dopamine D3 receptors seem to play a key role in the control of drug-seeking behavior. The imaging of their regional density with positron emission tomography (PET) could thus help in the exploration of the molecular basis of drug addiction. A fluorine-18 labeled D3 subtype selective radioligand would be beneficial for this purpose; however, as yet, there is no such tracer available. The three candidates [(18)F]1, [(18)F]2a and [(18)F]2b were chosen for in vitro and in vivo characterization as radioligands suitable for selective PET imaging of the D3 receptor. Their evaluation included the analysis of radiometabolites and the assessment of non-specific binding by in vitro rat brain autoradiography. While [(18)F]1 and [(18)F]2a revealed high non-specific uptake in in vitro rat brain autoradiography, the D3 receptor density was successfully determined on rat brain sections (n = 4) with the candidate [(18)F]2b offering a Bmax of 20.38 ± 2.67 pmol/g for the islands of Calleja, 19.54 ± 1.85 pmol/g for the nucleus accumbens and 16.58 ± 1.63 pmol/g for the caudate putamen. In PET imaging studies, the carboxamide 1 revealed low signal/background ratios in the rat brain and relatively low uptake in the pituitary gland, while the azocarboxamides [(18)F]2a and [(18)F]2b showed binding that was blockable by the D3 receptor ligand BP897 in the ventricular system and the pituitary gland in PET imaging studies in living rats.
EVALuna2:13864